Hitting Close to Home: The Effect of COVID-19 Illness in the Social Environment on Psychological Burden in Older Adults - Richter, Lukas; Heidinger, Theresa (Frontiers in Psychology, 2021)
This study examines the impact of Covid-19 experience of infection in the individual’s social environment on psychological burden controlling for a broad range of factors using data on an older population (50+ years). Based on the empirical evidence of pre-existing studies it is hypothesized, that psychological burden will increase concurrent to the severity of Covid-19 experience (tested positive, hospitalized, death) independent of the other stressors resulting from the pandemic such as a subjective sense of uncertainty or financial burden. Data of the Survey of Health, Aging and Retirement in EUROPE (SHARE), a European cross-national panel study, were used to examine this hypothesis. Besides Chi² test and Spearman’s rho a logistic regression model was constructed to test the hypothesized model. The study confirms that there is significantly higher risk for psychological burden by heightened Covid-19 severity in the social environment independent of multiple also significantly influential variables depicting stressors to everyday life of older people during the pandemic. The results point to the importance of multiple factors (social, financial, health, sociodemographic) which have significantly affected the psychological condition of the individual during the past year. Conclusively, the results illustrate the dilemma that infection and illness in the social circle, as well as countermeasures (social distancing) have negative consequences for our mental health.